1996
DOI: 10.1021/ma960650g
|View full text |Cite
|
Sign up to set email alerts
|

H NMR Characterization of Swelling in Cross-Linked Polymer Systems

Abstract: A 1H NMR method capable of determining the level of swelling of microscopic volume elements (about 20 μm in diameter) within cross-linked materials is described. The fact that it is a microscopic swell measurement makes it extremely useful for the characterization of the swelling heterogeneities which may exist within common network systems, such as core/shell or other morphologies. The method utilizes the differences in chemical shift between solvent absorbed into the cross-linked polymer and that of solvent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…The variation of T 1 with the correlation time of the local relaxation process describes a parabola with a frequency-dependent minimum, and for relatively slow local subsegmental motions, like those observed in the systems under study, one would expect T 1 to decrease as the subsegmental dynamics becomes faster. 35 The increase in T 1 observed with the increasing cross-linking density was in agreement with the expected trend for macromolecules and gels, 36 where, as the network becomes more cross-linked and rigid, the local subsegmental dynamics slows down leading to an increase in T 1 .…”
Section: ■ Results and Discussionsupporting
confidence: 84%
“…The variation of T 1 with the correlation time of the local relaxation process describes a parabola with a frequency-dependent minimum, and for relatively slow local subsegmental motions, like those observed in the systems under study, one would expect T 1 to decrease as the subsegmental dynamics becomes faster. 35 The increase in T 1 observed with the increasing cross-linking density was in agreement with the expected trend for macromolecules and gels, 36 where, as the network becomes more cross-linked and rigid, the local subsegmental dynamics slows down leading to an increase in T 1 .…”
Section: ■ Results and Discussionsupporting
confidence: 84%
“…These experimental results indicate that the spatial distribution of pendant vinyls (around the polymer radical), and hence that of cross-links in the gel, is highly heterogeneous. Inhomogeneous distributions of cross-links were experimentally observed by several methods. For example, in a uniaxially deformed gel, Bastide et al observed “butterfly patterns”, unusual scattering spectra arising from a spatially inhomogeneous deformation, which originates from an inhomogeneous cross-link distribution. For poly( N -isopropylacrylamide) gels, Shibayama et al observed that the scattering intensity from such a gel varies from position to position of the sample due to a nonuniform density distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The only reports found in literature that had recorded such multiple resonances of water are associated with biological tissues or polymer systems that are quite similar to the ion exchange resins or Nafion that were used in this study. These studies, however, did not address the dynamics of water lying outside the polymers or tissues.…”
mentioning
confidence: 99%